Displacement-based seismic performance assessment of multi-span steel truss bridges. (1st March 2022) - Nettis, Andrea; Iacovazzo, Pietro; Raffaele, Domenico; Uva, Giuseppina; Adam, Jose M.
Highlights: DBA algorithms for direct seismic performance assessment under a given seismic action are described. a pseudo-pushover approach and an equivalent viscous damping formulation for steel braced towers are proposed. recommendations for applying DBA and pushover approaches for steel truss bridges are presented. DBA approaches are used for fragility analysis considering the damage state of different structural components. Abstract: Simplified mechanics-based approaches for the seismic performance analysis are used for the risk assessment of large bridge portfolios. This study evaluates the applicability and effectiveness of displacement-based assessment (DBA) and nonlinear static procedures for multi-span railway steel truss bridges. Although built in the first part of the last century, these historical bridges are currently in service within the European railway networks, and their seismic performance is poorly investigated in the literature. Direct DBA algorithms and pushover-based procedures aimed at seismic performance assessment and fragility analysis of bridges are presented and tested within a set of case studies parametrically generated by using an archetype steel truss bridge. The first part of this study focuses on the seismic analysis of steel braced towers which, in many situations, compose the substructure of steel truss multi-span bridges. A simplified pseudo-pushover and an accurate equivalent viscous damping formulation are proposed to be used for the approximate performance displacement assessment of these structural components. The second part discusses the accuracy of the investigated approaches for multi-span steel truss bridges through comparisons with nonlinear time history analysis. The results of the parametric analysis are used to propose recommendations for an appropriate DBA or pushover-based strategy for the deterministic performance assessment and fragility analysis with reference to the damage state of the supporting towers or bridge serviceability in terms of superstructure transverse deformation.